2018
DOI: 10.1093/jnci/djy136
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Therapy Nonadherence and Discontinuation in Black and White Women

Abstract: Our results highlight important racial differences in ET-adherence behaviors, perceptions of benefits/harms, and shared decision making that may be targeted with culturally tailored interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
99
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 59 publications
4
99
0
Order By: Relevance
“…39,40 Stanton et al 41 surveyed 1371 patients and identified the relationship with the oncologist, the perceived ET necessity, and emotions regarding ET as factors associated with nonadherence to adjuvant ET. Wheeler et al 42 recently found an association between a lack of shared decision making and nonadherence in a cross-sectional survey from the Carolina Breast Cancer Study. Several other publications have highlighted the importance of patient-physician communication for adherence to treatment recommendations and patients' decisions about treatment.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Stanton et al 41 surveyed 1371 patients and identified the relationship with the oncologist, the perceived ET necessity, and emotions regarding ET as factors associated with nonadherence to adjuvant ET. Wheeler et al 42 recently found an association between a lack of shared decision making and nonadherence in a cross-sectional survey from the Carolina Breast Cancer Study. Several other publications have highlighted the importance of patient-physician communication for adherence to treatment recommendations and patients' decisions about treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For women with Endocrine Receptor positive breast cancer, endocrine therapy (ET) medication taken for five to ten years after completion of primary treatments can reduce the risk of cancer recurrence by up to 50% . However, even among those who initiate ET, many women struggle to maintain the daily regimen and some discontinue the medication completely, with estimates of non‐adherence rates ranging from 20% to 50% . Breast cancer recurrence is higher among Black women, young women and low‐income women; ET adherence is also lower in these vulnerable groups …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated the extent of ET non‐adherence in self‐report or claims data and have assessed reasons for non‐adherence qualitatively . Qualitative studies highlight a need to improve provider communication, particularly around the benefit of ET in recurrence risk reduction and need to help patients to better manage potential ET side effects .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cohort study, led by the Lineberger Comprehensive Cancer Center at the University of North Carolina at Chapel Hill, was published in the Journal of the National Cancer Institute …”
mentioning
confidence: 99%